Avaliação de desempenho para dispositivo móvel de dual-interface com conexão simultânea - SILVA, Fabio Pereira Ferreira da (2019)
With the exponential increase of heterogeneous wireless networks nowadays, there was a growing interest in the academic community, due to issues related to vertical handover problems. In order to guarantee the quality and continuity of service, used by mobile devices in the use of streaming, in the migration between networks with different technologies. The main objective of this work is to evaluate the quality of service and performance of a dual-interface device, which connect simultaneously to two heterogeneous networks (Wi-Fi and 4G). So that there is no competition in the exchange of packets between the two interfaces, thus proposing a viable solution to mitigate the impacts of vertical handover. The tool used to evaluate, perform and obtain the results was the Network Simulator. All the results were satisfactory, especially the results obtained by the traffic flow, where there was an improvement of one hundred percent in relation to the scenario using traditional mobile device. This is because traditional mobile devices use a single interface in connection with heterogeneous networks.